Final Year, Department Of Computer Science And Engineering K.S.R College Of Engineering (International Journal of Engineering and Computer Science, 2017)
In Automatic Speech Recognition (ASR), there is consistent growth since past five decades. ASR hasbeen developed in many spoken languages. This paper gives an overview of speech recognition system and itsapplications.